Update Management of Chikungunya - Mohammad Arif, Khan (Faridpur Medical College Journal, 2017)
Chikungunya is a viral infection first detected after an outbreak in Tanzania in 1952. Chikungunya virus (CHIKV) is a mosquito-transmitted alphavirus that belongs to the Togaviridae family. Incidence increases in rainy season. Exact pathogenesis is not clearly understood. Fever and arthralgia/arthritis is the striking feature of Chikungunya fever1. Few patient may develop neurological and other complication. Joint pain may persist for several years. Investigations for confirmation are Real-time PCR, Virus specific IgM antibodies and IgG antibodies. Treatments are supportive. Most patients recover completely. Death is very rare. Reducing natural & artificial water filled container habitats is the principal step of prevention. Faridpur Med. Coll. J. Jul 2017;12(2): 82-85